Association between exposure to road traffic noise and hearing impairment: a case-control study - Wang, Tang-Chuan; Chang, Ta-Yuan; Tyler, Richard S.; Hwang, Bing-Fang; Chen, Yi-Hung; Wu, Che-Ming; Liu, Chiu-Shong; Chen, Kuang-Chao; Lin, Chia-Der; Tsai, Ming-Hsui (Journal of environmental health science and engineering, 2021)
Purpose Noise pollution in urban areas is increasing steadily, and the study of road traffic noises and their effects on the auditory system was rare. This study investigated the potential effects of road traffic noise on auditory systems and hearing. Methods A case-control study recruited outpatients from the Otolaryngology department. The case group ( n = 41) had binaural hearing loss (HL) of standard pure-tone average(PTA)  ≥ 25 dB or high frequency PTA ≥ 25 dB, while the control group ( n = 39) had binaural hearing level of any frequency < 25 dB. Detailed otologic evaluations were performed. Between-group data were evaluated using logistic regression analysis. Case or control group was identified based on the audiogram. Results A total of 80 subjects were recruited, including 41 with hearing impairment and 39 as control. The mean exposure level of road traffic noise was significantly higher in the case group than the control group ( p = 0.005). A crude OR of 5.78 showed an increased risk of greater than 70 dB of road traffic noise on hearing impairment and tinnitus ( p < 0.001). The aOR of 9.24 ( p = 0.002) from a multiple variate analysis suggested that road traffic noise levels greater than 70 dB may have a damaging effect on hearing. Damaging effects on hearing persisted even after adjusting for confounders in the full multivariate model (aOR of 9.24 [95% CI: 2.198–38.869]; p = 0.002). Conclusions Exposing to road traffic noise greater than 70 dB showed an increased risk of damage to the auditory system. These results might help public health administrators and physicians to develop programs that address the health dangers of noise.